How do local factors shape transformation pathways towards climate-neutral and resilient cities? - Wolfgang Haupt; Peter Eckersley; Janne Irmisch; Kristine Kern (European Planning Studies, 2022)
We examine how local socioeconomic, institutional and political factors shape climate transformation pathways in 23 mid-sized German cities. We group our cities into three types: industrial cities (which may have experienced recent structural change), historic cities (in which a significant proportion of the buildings or landscape is under monument protection) and university cities (in which academic or research institutions play a major role in the local community). Drawing on document analysis and expert interviews, we find that budgetary constraints, weaker civil societies and lower levels of political support result in unfavourable structural conditions for successful transformations in industrial cities. Historic cities have often only limited options to change their built environments, but many have identified climate change as a major threat to their built heritage and are therefore keen to take action in climate adaptation. Lastly, university cities are further along the transformation pathways than the other city types, largely due to having more favourable economic conditions as well as greater support from civil society, politics and the local research community.
Keywords: 320; Historic cities; university cities; industrial cities; local climate governance; sustainable development; green cities